Cultural transfers, press and periodicals: from the Gazette d'Augsbourg to the Revue de Métaphysique et de Morale - Espagne, Michel [UNESP] (Univ Federal Uberlandia, 2024)
Research on cultural transfers aims to test new possibilities for going beyond the national framework of cultural history and examining the process of moving a cultural object from an initial context to a host context. The focus is on the role of the various mediators and the inevitable semantic reinterpretation of the import. Following the example of the Augsburger Zeitung and its most illustrious contributor, Heinrich Heine, the German press of the mid- 19th century focused on the social, political and artistic situation in Paris, the traditional laboratory of revolutions. In another sense, and like many other publications of the time, the Revue de M & eacute;taphysique et de Morale, at the end of the 19th century, was only interested in German philosophy - i.e., its way of thinking about the world - with the aim of drawing on their debates to develop his own philosophy, but without submitting to them. The article focuses on this circulation of ideas between the two countries through periodicals.
Keywords: resemantization; cultural transfers Germany/France; philosophical journals